EVALUASI KEKRITISAN LAHAN DAERAH ALIRAN SUNGAI (DAS) DAN MENDESAKNYA LANGKAH-LANGKAH KONSERVASI AIR - Sarminingsih, Anik (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
There are some critical lands scattered in watershed or basin in Indonesia.The existing area that wide enough tend to threat the potential critical land which still good in other land uses, as: forest, plantation, cultivation,  industry,  mining,  residential,  etc.  To  prevent  land  degradation  that increasing tends need effort for rehabilitating critical land. For potential critical land which still good enough needs prevent to watershed damage in order to watershed optimally functioned as producer and regular water. To obtain the aim was done by land conservation. Cisangkuy sub basin  is  apart  of  Citarum  basin.  Cisangkuy  sub basin  is  a  buffer  zone  in  fulfilling  water  for Kotamadya Bandung and  Kabupaten Bandung. Cisangkuy sub basin is critical which shown by erosion,  sedimentation  and  discharge  fluctuation.  The  erosion  in Bandung  valley  specially  in Cisangkuy sub basin is 163 ton/ha/yr. Sedimentation in Saguling reservoir is 3.02 – 4.32 billions m3 / year. Discharge fluctuation of minimum to maximum have range 49 - 394 m3/s. There are needed effort  of  land  and  water  conservations  by  structural  or  non  structural  to  suppor Gerakan Nasional - Kemitraan Penyelamatan Air (GNKPA)